Clinical features and pulmonary infections of diffuse alveolar hemorrhage in rheumatic disease patients - Carla Marina Román-Montes; Eduardo Briones-García; Shaul Ariel Navarro-Lara; Marco Antonio Ortiz-Bustamante; Iris Paola García-Herrera; Guillermo Arturo Guaracha-Basañez (PLoS ONE, 2025)
Introduction Diffuse alveolar hemorrhage (DAH) is an uncommon but potentially life-threatening pulmonary complication in patients with rheumatic diseases (RD). Immunosuppression, endothelial injury, and systemic inflammation may increase the risk of pulmonary infections, further complicating clinical management and worsening outcomes. Objective To describe the prevalence and factors associated with pulmonary infections in patients with DAH and RD. Methods We conducted a retrospective, cross-sectional study including patients diagnosed with DAH and underlying RD at a tertiary care center in Mexico between 2003 and 2023. A logistic regression model was used to identify factors associated with infection. Results Seventy-three patients with DAH were included; 31.5% had concurrent pulmonary infection. Systemic lupus erythematosus (68.5%) and ANCA-associated vasculitis (29%) were the most common underlying diseases. Evidence of hemorrhage in bronchoalveolar lavage was significantly more frequent in the infection group (76% vs. 48%; p = 0.02). Bacterial infection was the most common, occurring in 62% of cases, followed by fungal infection at 21%. The 30-day mortality rate was 10%, and infection was not an independent predictor of death. A multivariable logistic regression analysis revealed that male sex (OR 9.8; 95% CI: 2.7–35.3; p < 0.01) and IMV requirement (OR 8.8; 95% CI: 1.7–46.9; p = 0.01) were significantly associated with pulmonary infection. Conclusion Pulmonary infections are common in patients with DAH and RD. A relatively low short-term mortality rate was observed in this cohort. Male sex and IMV requirement were associated with infections. Early microbiological assessment and targeted therapy are crucial to optimizing outcomes in this vulnerable population.